P-111 Palliative care training for non-specialists: what happens in uk medical schools, primary care and hospital practice? how might deficits be addressed?. (1st March 2017) - Lawrie, Iain; Walker, Steven
Abstract : Background and purpose: PC has gained prominence in an effort to deliver quality care for people with end of life needs. 1 Non-specialist doctors provide the majority of such care. 2 Limited research suggests lack of preparedness and confidence for this role. 3 Similarly, weaknesses may exist in PC teaching at some medical schools. 4 Two parallel studies explore this further. Methodology: A survey of General Practitioners (GPs) and Hospital Doctors (HDs) examined education, knowledge and confidence in managing patients with PC needs. A second study surveyed UK medical school PC course organisers, focusing on teaching and organisation. Results were analysed for common themes. Results: Most GPs and HDs regularly saw patients with PC needs, and viewed PC positively. Self-assessment of competences was mixed. Participation in postgraduate PC education was low. Attending conferences does not change practice. Clinical attachments, shadowing opportunities, e-learning and textbooks are more likely to be beneficial. Undergraduates receive increased PC teaching time with greater curriculum integration and wider use of assessment however variability and areas of weakness exist. Concerns expressed include insufficient placements, teachers and funding. Doubts existed whether courses deliver quality training, adequately prepare doctors to care for PC patients, or fulfil General Medical Council requirements. Discussion and conclusion: PC teaching at medical school may be insufficient to equip doctors to care for patients with PC needs. There is a need for increased postgraduate training for non-specialists. To be effective, such training should be learner-centred, involve clinical scenarios and experiential learning, and recognition of barriers to PC education. References: . Riley J. A strategy for end-of-life care in the UK. BMJ2008;337:934–934 . Association for Palliative Medicine of Great Britain and Ireland. Curriculum for Undergraduate Medical Education . http://www.apmuesif.phpc.cam.ac.uk/index.php/apm-curriculum (accessed 7 July 2014). . Lloyd-Williams M, MacLeod RD. A systematic review of teaching and learning in palliative care within the medical undergraduate curriculum. Med Teach 2004;26:683–690. . Gibbins J, McCoubrie R, Forbes K. Why are newly qualified doctors unprepared to care for patients at the end of life? Med Educ 2011;45:389–399.